Principal’s Leadership Style in Influencing Teacher’s Performance at SMA Negeri Madang Suku I - Sutarjo, Sutarjo; Badeni, Badeni; Danim, Sudarwan; Purwandari, Elce (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
The leadership style of the principal in his capacity as a leader will determine the success of improving the performance of teachers under his leadership. The purpose of this study was to obtain data on (1) the principal’s leadership style, (2) the implementation of the principal’s leadership style, and (3) the constraints faced by the principal in improving teacher performance in schools. This study used a qualitative approach with descriptive methods, data collection techniques were carried out through interviews, observations, and documentation. This study shows that (1) the principal applies a situational leadership style in influencing his subordinates by seeing and understanding the background of each of his subordinates in making policies. (2) Implementation of the principal’s leadership style in influencing teacher performance, namely instructive, consultative, participatory, and delegative (3) the obstacles faced by school principals are the teacher’s ability to use “computer” technology, the lack of variation in the selection of learning methods carried out by school principal’s different teacher and subordinate background conditions.